FRI0538 Evaluation of factors that increase fracture risk in breast cancer. (15th June 2017) - Anand, A; Ghafouri, M; Bukhari, M
Abstract : Background: Women with breast cancer are at an increased risk of fractures. This is present in patients with both active and treated disease. In addition to established risk factors of fractures, patients with breast cancer are exposed to additional factors that further compromise bone strength. These factors primarily include: the malignancy interfering with bone metabolism and breast cancer treatments inducing bone loss. Objectives: To evaluate fracture risk in active and treated breast cancer patients, and to understand the role bone mineral density (BMD) plays in predicting fracture risk. Methods: The study population included breast cancer patients with active and treated disease referred to dual-energy X-ray absorptiometry (DEXA) scanning at the Royal Lancaster Infirmary between 2004–2015. Patients on aromatase inhibitors were excluded because of its' negative effect on oestrogen. From this population, we collected BMD measurements of the femur and lumbar vertebra. Alongside information on physical characteristics such as age, height, weight, body mass index (BMI), average tissue thickness, lean and fat mass were measured. To evaluate other precipitating factors known to increase fracture risk we included: smoking status, steroids use, alcohol, family history of fractures, diagnosis of rheumatoid arthritis and secondary osteoperosis. Data analysis was done on R 3.3.2 software. Odds ratios were calculated using logistic regression and age adjusted models were compared using the likelihood ratio test. Categorical data was analysed using Chi squared and Fischer's exact test, while continuous data was analyzed using t-test. Results: The study population was a total of 306 patients with a mean age of 63.6 years. 146 of the study group had active disease, while 160 patient were breast cancer survivors. Of the total population 87 (28%) had sustained at least one fracture. Active breast cancer insignificantly increased fracture risk in comparison to the cancer survivor population ( OR=1.330, 95% CI=0.801–2.218, p=0.271) . Physical characteristics that significantly increased fracture risk included increased age and decreased average fat percentage (Table 1 ). BMD reduction in the femoral neck and all vertebrae significantly increased odds of having a fracture (Table 2 ). External factors such as smoking status, alcohol consumption, family history and steroid use had no significant effect. Conclusions: In conclusion, this study emphasizes DEXA measurements are the best predictive tool for fractures in breast cancer patients. Thus further supporting the need for increased BMD surveillance for those diagnosed with breast cancer who are not on aromatase inhibitors. References: Body J: Increased fracture rate in women with breast cancer: a review of the hidden risk. Body BMC Cancer 2011, 11:304. R Core Team (2016). R: A language and environment for statistical computing. R Foundation for Statistical Computing, Vienna, Austria. Disclosure of Interest: None declared